2011
DOI: 10.2209/tdcpublication.52.223
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Periodontal Therapy at Tokyo Dental College Suidobashi Hospital: A Statistical Profile in 2010-2011

Abstract: The aim of the present study was to investigate the profile of surgical periodontal therapy performed at the Suidobashi Hospital of Tokyo Dental College, during the period of April 2010 through March 2011. A total of 112 periodontal surgeries in 69 patients (mean age: 51.4 years; 28 men and 41 women) were registered for the data analysis. The surgical interventions performed by 17 dentists comprised 79 cases of open flap debridement, 27 cases of periodontal regenerative therapy with enamel matrix derivative an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
(15 reference statements)
0
2
0
Order By: Relevance
“…A surgical record form 8) was used to assess the profile and outcome of surgical periodontal therapy. The form contained the following items: patient demographics, systemic condition, smoking status, surgery type and sites, and periodontal parameters of the surgical site.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A surgical record form 8) was used to assess the profile and outcome of surgical periodontal therapy. The form contained the following items: patient demographics, systemic condition, smoking status, surgery type and sites, and periodontal parameters of the surgical site.…”
Section: Methodsmentioning
confidence: 99%
“…It is equally important to consider the feasibility of implementing the treatment recommendations in one's own practice setting. Previously, we have reported the profile of surgical periodontal therapy at Tokyo Dental College Suidobashi Hospital 8) . We found that the initial periodontal therapy implemented prior to surgery was effective in improving the periodontal condition of patients.…”
Section: Introductionmentioning
confidence: 99%